Damage Model of Basalt-Fiber-Reinforced Cemented Soil Based on the Weibull Distribution - Lina Xu; Runze Zhang; Lei Niu; Chenhui Qi (Buildings, 2023)
This study investigates the mechanical performance and a constitutive model of basalt-fiber-reinforced cemented soil (BFRCS) containing 0%, 0.1%, 0.3%, 0.5%, and 0.7% basalt fibers with lengths of 3, 6, 12, 20, and 35 mm, respectively. Unconfined compressive strength tests were used to examine the mechanical performance of BFRCS with varying basalt fiber contents and lengths. The test results demonstrate that the basalt fiber content of optimal quality is 0.1%, and that the fiber distribution uniformity and density have a significant impact on the strength of BFRCS. Based on the Weibull distribution of BFRCS for the degree of damage, a damage model for BFRCS, accounting for the fiber length and fiber content, is proposed here. Moreover, in this study we explored the relationship between the scale parameter as well as shape parameter of the Weibull distribution and fiber content as well as length. Furthermore, the evaluation methods for the mechanical properties of BFRCS according to the scale and shape parameters of the Weibull distribution are discussed. The results suggest that the proposed constitutive model captures the compressive stress–strain relationship of BFRCS; the theoretical results are in strong agreement with the data obtained.